Compensation as a tool for attracting employees to the military organization - Čurčija, Slobodan; Trnski, Mladen (Crisis Management Days, 2024)
Every company aims to attract employees who can contribute to its success. However, in today's business environment, simply posting job ads isn't enough to secure top talent. Instead, companies need to target specific candidates, advertise job openings effectively, and leverage their marketing efforts to highlight the opportunities they offer. One potential strategy is to enhance the compensation package to attract skilled candidates. While attracting for military organizations wasn't a significant challenge in the past, factors like technological advancements, competition from civilian sectors, and the stress of combat operations have made it increasingly difficult to attract new recruits, especially those with specialized skills. Furthermore, the lack of soldiers and officers candidates has become a serious problem in the execution of the missions of military organization. To address this, military organizations are exploring ways to offer more appealing benefits and incentives to potential candidates. Regarding everything previously mentioned, the paper investigates the impact of elements of compensation on attracting employees to the military organization. Accordingly, the research goal is to explore and analyze the impact of compensation on the attraction of employees to a military organization. Based on this aim, a fundamental hypothesis is formulated for this study, and it states: compensation and its aspects have a significant influence on the attraction of employees to a military organization. To explore the aforementioned hypothesis and fulfill the research goals, various scientific research methods were employed in this study. Initially, the descriptive method was used to describe and explain variables related to the hypotheses. Additionally, the comparative method was applied to compare the subject variables, processes, phenomena, and relationships. Throughout the study, methods such as generalization, specialization, analysis, synthesis, induction, deduction, abstraction, and concretization were also utilized to deepen the understanding of the research subject. The results obtained from the research show that, in addition to traditional direct financial elements such as salaries, some other indirect financial elements such as benefits have an impact on the increased interest in entering a military service. In addition, the results indicate that individual countries have more closely been studying the reasons for a decreased interest joining military forces, while trying to create short-term and long-term strategies to overcome that situation. The paper also considers attracting employees to civil firms.